2010
DOI: 10.1038/ismej.2010.130
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the distribution of nitrogen-cycling microbial communities at the landscape scale

Abstract: Little information is available regarding the landscape-scale distribution of microbial communities and its environmental determinants. However, a landscape perspective is needed to understand the relative importance of local and regional factors and land management for the microbial communities and the ecosystem services they provide. In the most comprehensive analysis of spatial patterns of microbial communities to date, we investigated the distribution of functional microbial communities involved in N-cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
220
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(251 citation statements)
references
References 56 publications
23
220
2
6
Order By: Relevance
“…In a large-scale field study, Enwall et al [67] found a positive relationship between soil Cu content and the abundance of nirK genes. Thus, Cu plays a key role in both NO 2 2 and N 2 O reduction [68]. With approximately 40 per cent of Europe's arable soils being Cu deficient (less than 2 mg Cu kg 21 ), the potential for N 2 O mitigation (with a simultaneous crop yield increase) is high.…”
Section: Nitrous Oxide Emissions From Soilsmentioning
confidence: 99%
“…In a large-scale field study, Enwall et al [67] found a positive relationship between soil Cu content and the abundance of nirK genes. Thus, Cu plays a key role in both NO 2 2 and N 2 O reduction [68]. With approximately 40 per cent of Europe's arable soils being Cu deficient (less than 2 mg Cu kg 21 ), the potential for N 2 O mitigation (with a simultaneous crop yield increase) is high.…”
Section: Nitrous Oxide Emissions From Soilsmentioning
confidence: 99%
“…For the latter, a recent DNA fingerprinting experiment showed that CopA genes were strongly influenced by pH (Lejon et al, 2007). pH has also been shown to affect both ammonia-oxidizing archaea and ammonia-oxidizing bacteria (Bru et al, 2010). Therefore, the correlation between pH and amoA-ammonia-oxidizing archaea/amoA-ammonia-oxidizing bacteria ratios was examined.…”
Section: Microbial Mediation Of Responses To Warmingmentioning
confidence: 99%
“…pH was shown to be a major factor in shaping soil microbial community at the global scale (Fierer and Jackson, 2006) and to affect certain genes such as those involved in nitrification (Bru et al, 2010). Pearson's correlation tests indicated that a total of 65 genes spanning a number of categories such as the C cycle, N cycle, antibiotic and metal resistance were significantly (r ¼ À 0.62B0.84, Po0.010) correlated with pH (Supplementary Table S7).…”
Section: Microbial Mediation Of Responses To Warmingmentioning
confidence: 99%
“…Subsequently, the spatial variation of pollutants and other soil chemical parameters may regulate the spatial patterns of microbial communities (Tö rneman et al, 2008;Bengtsson et al, 2010). Association between spatial patterns of environmental factors and the distribution of microbial taxa as well as their activities can be elucidated via geostatistical modelling (Philippot et al, 2009;Bru et al, 2010;Enwall et al, 2010;Wessén et al, 2011). Furthermore, the choice of taxonomic level to address the microbial community responses is a crucial issue.…”
Section: Introductionmentioning
confidence: 99%